2010
DOI: 10.21225/d5rp4b
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Educational Needs of Nurses in Telepractice: A Descriptive Exploratory Study

Abstract: Although some nursing bodies have recognized nursing telepractice as a specialty, with its own knowledge, skills, and attitudes, there is little documented evidence of the education- al needs of Canadian nurses working in tele- health. However, now that telehealth has been recognized as a partial solution to Canada’s health-care challenges, the area requires our attention as educators. This article is based on a study that explored the educational needs of 138 telehealth nurses practising across Canada; partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…This study adds to that literature, as it not only measured nurses' confidence in operating a certain IT device, but subsequently whether they felt able to integrate this device into health care, for example, through the skill "able to create a confidential environment and a pleasant atmosphere in video conferencing. " Carter, Hudyma, and Horrigan (2010) explored the educational needs in telepractice (i.e., the delivery of care provided via information and communication technologies) of nurses in Canada and mentioned that providers of telehealth education programs could include colleges, universities, nursing associations, telehealth organizations, or hospitals. For hospitals, the results of this study can be used as a starting point in the development of continuing education programs by considering which KSAs were scored as moderate or low (further discussed in the section Implications for Continuing Education).…”
Section: Integration With Prior Researchmentioning
confidence: 99%
“…This study adds to that literature, as it not only measured nurses' confidence in operating a certain IT device, but subsequently whether they felt able to integrate this device into health care, for example, through the skill "able to create a confidential environment and a pleasant atmosphere in video conferencing. " Carter, Hudyma, and Horrigan (2010) explored the educational needs in telepractice (i.e., the delivery of care provided via information and communication technologies) of nurses in Canada and mentioned that providers of telehealth education programs could include colleges, universities, nursing associations, telehealth organizations, or hospitals. For hospitals, the results of this study can be used as a starting point in the development of continuing education programs by considering which KSAs were scored as moderate or low (further discussed in the section Implications for Continuing Education).…”
Section: Integration With Prior Researchmentioning
confidence: 99%
“…It can be used to alleviate the shortage of healthcare practitioners; improve access to specialist physicians; reduce the costs of accessing healthcare services by reducing the need to travel for consultation; and provide support to rural general practitioners and community service therapists, thereby improving retention in rural communities. [2][3][4][5][6] One of the suggested strategies to promote telehealth at a national level within developing countries is to introduce telehealth into the education and training programmes of healthcare professionals, both undergraduate and postgraduate, so that they are aware of, and can use, telehealth methods to provide healthcare to their patients. [7] The benefits associated with telehealth provide impetus for student and professional training across the healthcare disciplines.…”
Section: Researchmentioning
confidence: 99%
“…A review of the literature identified key knowledge areas required for effective telehealth practice that should be included in a telehealth course: computer competence and literacy; [3,25,26] understanding of ethical and legal issues; [25][26][27][28][29] understanding of the protocols and standards that guide good practice; [30] and data management, specifically relating to online transmission, retrieval and storage of data. [29] It is important to put these issues into the SA context in view of current healthcare constraints, service delivery issues and the infrastructure requirements of a telehealth service.…”
Section: Researchmentioning
confidence: 99%
“…The main purpose of these meetings was to share and discuss focus group findings from the earlier training needs analysis (Guise, Husebø, Storm, Moltu, & Wiig, 2016;Guise & Wiig, unpublished results), in the aid of enabling initial decision-making on training objectives relevant to each organization. In addition, discussions on training objectives were informed by broad literature recommendations on the knowledge, skills, and competencies required for sound provision of telecare services such as virtual visits (e.g., Basu et al, 2010;Brewster et al, 2014;Carter, Horrigan, & Hudyma, 2010;Pellegrino & Kobb, 2005;Sevean, Dampier, Spadoni, Strickland, & Pilatzke, 2008). Furthermore, findings from systematic reviews on the safety and quality of telecare services (Guise et al, 2014) and common clinical uses for virtual visits also contributed knowledge to these discussions.…”
Section: The Safer@homedsimulation and Training Action Research Studymentioning
confidence: 99%